ANALISIS KANDUNGAN HORMON TIROKSIN DENGAN METODE ELISA PADA INDUK BETINA KEPITING BAKAU (Scylla serrata) - Iromo, Heppi; Farizah, Nuril (Jurnal Harpodon Borneo, 2014)
The mud crab was high commercial value. To develop hatchery techniques for female reproduction were investigated. Experiments were studi of thyroxine hormone for female reproduction in stages vitellogenesis. Thyroxine hormone is known to be controlled growth, and mature ovary. The occurrence of thyroxine hormone, female reproduction is yet to be determeined. The level of thyroxine hormon in ovary, hemolymp and the hepatopancreas of the mud crab female were reproduction analyzed in different vitellogenic in order to establish a correlation hormon profile and stages of vitellogenesis. It was observed that the level of thyroxine hormon increased steeply in the tissues of vitellogenesis. The higest concentration of thyroxine hormon was seen in ovary then hepatopancreas and hemolymp.Keywords : Female reproduction, thyroxine hormone, vitellogenesis.